International Migration to Russia: The Gender Aspect - Pavel S. Seleznev; Fedor I. Arzhaev; Alexandra D. Zvereva (Review of Business and Economics Studies)
International population migration from an economic point of view has a significant impact not only on the labor markets of countries participating in it, but also on their economies and societies. On the one hand, international migration flows contribute to the development of trade and economic relations between countries. However, on the other hand, they can cause undesirable tensions within the host country's society and have negative economic consequences. This study aims to analyze the main factors influencing the decision to migrate to Russia through econometric modeling. The relevance of this study is determined by the growing migration pressure in the Russian Federation up to 2024 and the need to better understand this phenomenon within the context of the Russian economy. In the context of the changing migration policy, the study is even more relevant. The novelty of this study lies in the applied migration research methodology, which has revealed the relationship between male and female international migration to Russia over time, as well as the results obtained from this research. The main findings of the study include identifying and describing a “vicious cycle of male labor international migration” in both developed and developing countries. It also proves that in Russia, men's international migration is driven by job search, while women follow their partners and only then find employment and change their status from a migrant to a family reunification migrant or a migrant worker. Additionally, it is demonstrated that the Russian Federation is characterized by the development of "migration attractors," which makes it challenging to implement effective migration policies.